Influência da irradiação na composição da farinha de casca de pitaya vermelha (Hylocereus Costaricensis) - Santos , André Leonardo dos (Universidade Federal do Tocantins, 2021)
Fruit has been targeted by consumers looking for a healthier way to eat. With the large consumption of fruits and their processing to produce juices, ice creams, frozen pulp, jellies, etc., a significant amount of agro-industrial waste is generated, among them peelings, stems and fruit seeds. Irradiation is a non-thermal technological process, but it has a greater versatility than processes that use heat, being adopted by more than 50 countries as a sanitary and phytosanitary processing method, covering more than 60 foods and food products. In this context, the objective of the present work was to characterize the irradiated flour of red pitaya shell (Hylocereus costaricensis), from the physical, chemical, technological, nutritional, antinutritional and antioxidant profile points of view. The flours were irradiated with 0, 1, 2 and 4 kGy. The highest values for humidity were found in samples submitted to 2 kGy (6.46%). There was no significant difference for protein values. The sample submitted to 2 kGy obtained a 55.5% increase in lipid levels. The ash contents varied between 12.95% and 14.04%. The maximum value for the total energy value and pH were 328.15 kcal and 4.47, respectively. No presence of anti-nutritional compounds and tannins were detected. The use of irradiation increased the levels of vitamin C, phenolic compounds and antioxidant potential (FRAP). The fiber content was maintained with an average of 56.54%. There was no statistical difference in the color of pitayas bark flour. The carbohydrate profile revealed that sucrose is the predominant sugar in flours with a 0.995% content. FTIR analysis showed that irradiation did not change the sample spectra. The study revealed that the irradiation process caused few changes in pitaya husk flours, making it a good alternative for flour preservation.